Fiscal and Welfare Impacts of Electricity Subsidies in Central America - Hernández Oré, Marco Antonio; Sánchez, Luis Álvaro; Sousa, Liliana D.; Tornarolli, Leopoldo (Washington, DC: World Bank, 2017)
Central American countries spend approximately one percent of their aggregate gross domestic product subsidizing residential electricity consumption. This amount is comparable with what these countries spend on education and social assistance. The pressure that electricity subsidies exert on government budgets is particularly high when international energy prices rise. Electricity subsidies also provide perverse incentives for the overconsumption of electricity as households do not pay the true cost of their consumption, which in turn reduces incentives to increase energy efficiency. This book answers key questions regarding residential electricity subsidies in Central America. In particular: How do the subsidy mechanisms function in each country? What are their fiscal costs? Are these subsidies good value for the money? How efficient are subsidies in reaching households in need, and what drives this efficiency? What are the reform options?